Basic Life Support Training for Posyandu Cadres in The Bumi Indah Residential Area of The Sakura Cluster, Tangerang District - Zahrah Maulidia Septimar; Imas Sartika; Ahmad Kurtusi; Azzahra Ma’ruf Fiana (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
One of the causes of the high mortality rate due to cardiac arrest that occurs outside thehospital is due to late help, which we still encounter today due to lack of responsiveness,lack of skills, and lack of public understanding of first aid measures when finding someonewith respiratory arrest or cardiac arrest. before being sent to health services. One of theimportant reasons, people need to know and have sufficient supplies to perform qualityCardiopulmonary Resuscitation (CPR) is to anticipate people at home experiencingemergency conditions. The purpose of this community service activity is to carry out basiclife support activities using CPR techniques. The target of the service is the integratedhealth service at the Bumi Indah Cluster Sakura. The activity is carried out in one day onJuly 17, 2022, the stages of activity are preparation, implementation, and evaluation.Preparation was carried out by conducting a preliminary survey to see conditions in thefield and obtaining permission from RW 19 for the facilities used. Implementation is doneby distributing pretest questionnaires, delivery of materials, CPR practice, and post-test.Evaluation of activities is carried out for each stage by collecting and concluding data fromeach stage of activity. The result of the activity is the implementation of training activitiesfor providing Basic life support to integrated health services. Implementing lecturer andstudent activities and collaborating with HIPGABI Banten.